Hubungan Motivasi, Lingkungan kerja, dan Kompensasi Terhadap Kepuasaan Kerja Karyawan PT Karya Bersama Anugerah, Tbk Balikpapan - Cindy Crawford Kilapong; Didik Hadiyatno; Rahajeng Cahyaning Putri Cipto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the effect of Return on Assets, Current Ratio, and Sales Growth on financial distress in companies in the tourism and recreation sub-sector listed on the Indonesia Stock Exchange during the post-COVID-19 recovery period (2022–2024).This research uses a quantitative approach with a purposive sampling technique. The final sample consists of 75 observational data. The data analysis method used in this study is logistic regression analysis using IBM SPSS version 24. Originality/Novelty: The novelty of this research lies in its analytical focus on the tourism and recreation sector during the post-pandemic recovery period of 2022–2024, which has been relatively underexplored empirically. This study also integrates three key financial indicators to predict financial distress conditions. The results indicate that Return on Assets (ROA) and Sales Growth (SG) have no significant effect on financial distress. Meanwhile, Current Ratio (CR) partially has a significant effect. Simultaneously, ROA, CR, and SG have a significant effect on financial distress.: These findings indicate the importance of liquidity in maintaining corporate financial stability during the post-pandemic period and provide a reference for corporate management and investors in more accurately identifying distress risks